New experimental dataset for partial dam-break floods over mobile beds. Issue 1 (2nd January 2018) - Qian, Honglu; Cao, Zhixian; Liu, Huaihan; Pender, Gareth
ABSTRACT: An experimental investigation is presented on partial dam-break floods over mobile beds, with different bed sediment compositions and initial upstream and downstream water levels. Detailed measurements were carried out, including water level evolution, final bed topography and bed surface sediment composition. Intense scour occurred immediately downstream from the dam, followed by significant deposition and small bed forms which were only observed in cases with non-uniform sediment. Also, final bed sediment surface showed a general coarsening trend in the intense scour and deposition areas and a coarse-fine-coarse structure in the remaining reach with small bed forms. The effects of the bed sediment composition and of the difference between initial upstream and downstream water levels on bed deformation are evaluated. This work facilitates new understanding of dam-break floods over mobile beds especially with non-uniform sediment, and provides a new experimental dataset which can be exploited to underpin the development of mathematical models.